STRATEGI PENDAMPINGAN SPIRITUAL ANAK DIFABEL KRISTEN DI BALAI SENTRA EFATA KUPANG - Nigha, Johanes Marno; Aseleo, Kurniawati; Rita, Rita; Afi, Bilsan Atarot; Magdalena, Emi (Jurnal Dedikasi Pendidikan, 2025)
Spiritual assistance for children with disabilities at the Efata Center in Kupang faces significant challenges due to limited resources and existing approaches. This research aims to explore the perceptions of social workers and religious counselors regarding the spiritual assistance strategies that have been implemented. The methodology used is focused group discussions (FGD) with six participants, consisting of social workers and religious counselors at the Efata Center.The research findings indicate that the process of spiritual assistance for children is influenced not only by a lack of religious knowledge brought from home but also by the need for a more holistic approach. The study emphasizes the necessity for state social institutions like the Efata Center to provide adequate spiritual assistance and regular counseling for social workers and religious counselors. Furthermore, utilizing richer spiritual learning methods, including interactive media, is crucial in developing the spirituality of individuals with disabilities.This research recommends enhancing the capacity of educators and religious counselors in implementing more effective assistance strategies to support the spiritual development of children with disabilities